Geoscience Job Advertisements as a Barrier to Employment for People With Disabilities - G. W. Shafer; K. Viskupic; A. E. Egger (Earth Science, Systems and Society)
Individuals with physical disabilities are largely underrepresented in the geoscience workforce. In this study, we analyzed over 2,500 job advertisements (ads) for entry-level geoscience positions across 19 industries to assess how inclusive the United States job market is for people with physical disabilities. We evaluated each ad’s Equal Opportunity Employer (EEO) and accommodation statements to create a measure of geoscience employers’ inclusive practices for people with disabilities. We coded each ad for instances where physical abilities (e.g., traversing rough terrain, driving a vehicle, lifting heavy objects) were listed as required or preferred qualifications and whether these abilities matched the core job function. A significant proportion of job ads (44%) did not include EEO statements, and of those that did, the language used was minimal or abbreviated. Additionally, only 18% of ads mentioned accommodations for people with disabilities. Of the ads that required physical abilities, only 19% requested physical abilities that matched the core job function. Students exploring their career options or applying for entry-level jobs may feel disadvantaged, restrict their applications, or dismiss geoscience careers if they have physical limitations, or if they perceive that the work environment is not inclusive. Overall, online geoscience ads could benefit from adding or modifying equal opportunity employment and accommodations statements to reflect a more inclusive workplace and could explicitly link requested physical abilities to the job description. These results could help employers consider possible modifications to their job advertisements and explore alternative strategies to promote a more inclusive geoscience workforce.